Esterification of Glycerol With Oleic Acid Over Hydrophobic Zirconia-Silica Acid Catalyst and Commercial Acid Catalyst: Optimization and Influence of Catalyst Acidity - Kong, Pei San; Pérès, Yolande; Wan Daud, Wan Mohd Ashri; Cognet, Patrick; Aroua, Mohamed Kheireddine (Frontiers in Chemistry, 2019)
Catalytic esterification of glycerol with oleic acid (OA) was optimised over hydrophobic mesoporous zirconia-silica heterogeneous acid catalyst (ZrO2-SiO2-Me&Et-PhSO3H) and benchmarked with commercial catalysts (Aquivion and Amberlyst 15) in order to examine the effect of catalyst acidity on conversion, yield and product selectivity. The process optimisation results showed an 80% conversion with a 59.4% glycerol mono-oleate (GMO) and 34.6% glycerol dioleate (GDO) selectivities corresponding to a combined GMO and GDO selectivity of 94.8% at equimolar OA-to-glycerol ratio, 160 °C reaction temperature, 5 wt% catalyst concentration with respect to the OA weight and 4 h reaction time. This work reveals that the hydrophobic and mild acidic ZrO2-SiO2-Me&Et-PhSO3H catalyst outperformed Amberlyst 15 and Aquivion with a yield of 82 % and GMO selectivity of 60 %. It is found that catalyst acidity is a key parameter for catalytic activity and conversion rate. Nevertheless, high acidity/acid strength reduced the product yield in the glycerol esterification of OA.